Smart Tax Administration - Bird, Richard (World Bank, Washington, DC, 2012)
The 'smartest' development policy needs to be underpinned by 'smart' tax policy. However, the best tax policy in the world is worth little if it cannot be implemented effectively. What can be done, to a considerable extent, inevitably determines what is done. Increasing tax revenues requires an effective tax administration: new taxpayers must be identified and brought into the tax net, and new collection techniques developed. Implementing such changes invariably takes time.